Особливості процесів міграції населення України - Процик, І. С.; Кара, Н. І.; Protsyk, I. S.; Kara, N. I. (Видавництво Львівської політехніки, 2005)
У статті проаналізовано основні показники, які характеризують населення України, зокрема рівень безробіття, мобільність громадян по регіонах, рівень народжуваності та смертності. Наведено інформацію про досвід роботи українців за кордоном за регіонами, тенденції міжнародної міграції та міграції населення з України, виокремлено найбільш популярні країни для міграції. Визначено чинники, які зумовлюють міжнародну міграцію населення і визначають її світові тенденції і масштаби та основні типові причини міграції українців. Визначено країни, які суттєво послабили умови перебування для українських трудових мігрантів з метою їх більшого приваблення.

The article analyzes the main indicators that characterize the population of Ukraine, in particular unemployment, mobility by region, birth rate and mortality, in particular, the forecast of the population of Ukraine and in terms of two categories such as ages 0–14 years and 65 years and older. The information on the experience of Ukrainians working abroad by regions during 2002 and 2020, trends of international migration for the period 1990–2020 and migration of the population from Ukraine are given. As it shown, the lowest figure was in 2010 and amounted to 5.4 million people living outside the country. The decline in the number of Ukrainian labor migrants abroad has doubled in the last 15 years, in 2010 - due to the global economic crisis and the emergence of problems with employment of migrants abroad and in 2020 – declining trends directly depended on global restrictions and lockdown citizens lost their jobs and were forced to return home. The factors of the international migration of the population and determine its global trends, scale and directions and the main typical causes of migration of Ukrainians, which have the greatest impact on the process of change of the country, were determined. Sometimes it is difficult to determine the main reason for moving and mostly migrants are driven by a combination of reasons and factors. Many foreign countries declare their interest in Ukrainian labor migrants and are ready to introduce additional measures to attract and retain foreign workers in the market. The countries that have significantly weakened the living conditions for Ukrainian labor migrants in order to attract them more, including Poland, Slovakia, the Czech Republic, Hungary, Germany and other countries, have been identified, and the main measures implemented have been described. The migration processes in Ukraine that took place after February 24, 2022 and are related to martial law are also described. As of April 22, according to official figures alone, nearly 13 million Ukrainians had been forced to flee their homes, including about 7.7 million internally displaced persons and more than 6 million people crossing the border into Ukraine. This is almost 32% of the population of Ukraine.
Peculiarities of Ukrainian population migration processes
Keywords: міграція; трудова міграція; причини міграції населення; заходи по залученню мігрантів; аналіз міграційної ситуації в Україні; рекомендації по поверненню своїх громадян; migration; labor migration; reasons for population migration; measures to attract migrants; analysis of the migration situation in Ukraine; recommendations for the return of its citizens; 314.15